Aline Estèves, Poétique de l'horreur dans l'épopée et l'historiographie latines, Bordeaux (Ausonius Éditions) 2020 (Collection Scripta Antiqua 127), 471 S., ISBN 978-2-35613-366-3 (brosch.), € 30,–. - Tomcik, Melissande (KLIO: Beiträge zur Alten Geschichte, 2022)
1 471 Aline E(stèves)'s monograph, based on her 2005 doctoral thesis, delivers exactly what the title promises, a detailed study of the literary - and often poetic - devices used to describe horror in Latin epic and historiography. Throughout the book, E. regularly compares and contrasts the usage of horror in epic and historiography. Aline Estèves, Poétique de l'horreur dans l'épopée et l'historiographie latines, Bordeaux (Ausonius Éditions) 2020 (Collection Scripta Antiqua 127), 471 S., ISBN 978-2-35613-366-3 (brosch.).